The venezuelan criminal law area: Towards transformational leadership management from complexity - Rodríguez Millán, Jesús (GACETA DE PEDAGOGÍA, 2019)
In modern times, a criminal judge is required to be a leader capable of achieving collective goals and purposes. This style of leadership is known as transformational leadership. The justice system functions as an executing arm of the regulatory body that stipulates a country's legal framework, and cannot be left behind with old management paradigms typical of public management. Modern management with new visions is necessary to provide transformations from the collective. For the approach of this research, the characteristics of qualitative research were taken, starting from a phenomenological approach to deal with reality and the hermeneutical method presented by Husserl. Three key informants were consulted: a judge, a secretary and an assistant, to whom an in-depth interview was applied, reaching analysis units that resulted in a closure.